The ecclesiastic status of the see of Tomis between the 4th and 6th centuries: Reading notes on Ionuț Holubeanu’s research (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
The ecclesiastical structure of Roman Scythia was widely discussed among the specialists since the end of the 19th century. Ionuț Holubeanu’s contribution, especially his volume discussing the ecclesiastical organisation of both Scythia and Moesia Secunda shed a new light on the issue, especially regarding the status held by the see of Tomis between the fourth and sixth centuries. Although remarkable in its analysis of the primary sources, his work lacks an extended archaeological review, problem that faults the reliability of a part of his conclusions. This paper, presented in a reading notes format, engages with his study, aiming at a critical reassessment of the methodology used by Holubeanu in the particular topic regarding the status of the Tomitan see through the 4th-6th centuries. His work is confronted both with primary sources and secondary literature aiming to help with the understanding of the complex issue of Christian developments in the ancient Dobrudja.